Information Sharing in Credit Markets - PAGANO, MARCO; JAPPELLI, TULLIO (Journal of Finance, 1993)
ABSTRACT We present a model with adverse selection where information sharing between lenders arises endogenously. Lenders' incentives to share information about borrowers are positively related to the mobility and heterogeneity of borrowers, to the size of the credit market, and to advances in information technology; such incentives are instead reduced by the fear of competition from potential entrants. In addition, information sharing increases the volume of lending when adverse selection is so severe that safe borrowers drop out of the market. These predictions are supported by international and historical evidence in the context of the consumer credit market.